Diversity of the Ghrelin gene in Nigeria’s Fulani and Yoruba Ecotype Chickens (2024)
Ghrelin (GHRL) is a novel 28-amino acid gut-brain peptide linked to a gene associated with the regulation of growth hormones in birds. This study was carried out to investigate the polymorphism of the Ghrelin gene in Fulani and Yoruba ecotypes chickens in Nigeria. Blood samples were collected from seventy-eight (78) Nigerian indigenous chickens comprising of 41 Yoruba ecotype chickens and 37 Fulani ecotype chickens. Polymerase Chain Reaction-Restriction fragment length polymorphism (PCR-RFLP) method was used and the MboII restriction enzyme cut site 71 of the ghrelin and genetic structure were determined. Population structure was analyzed using allele and genotype frequencies, heterozygosity and genetic variation metrics. Two alleles (C and T) and three genotypes (CC, CT and TT) were observed. In the Yoruba Ecotype, the allele frequencies were C (0.34) and T (0.66) respectively while C (0.45) and T (0.55) were observed in the Fulani ecotype and the overall population was C (0.39) and T (0.61). The genotype frequencies obtained were; in the Yoruba ecotype, CC (0.10), CT (0.48), and TT (0.41) were observed. In the Fulani ecotype, CC (0.22), CT (0.45), and TT (0.32) were also observed, and in the overall population CC (0.15). CT (0.47) and TT (0.37) were observed. FIS values for the Yoruba ecotype (-0.0847) and Fulani ecotype (0.00702) reflects random mating and inbreeding respectively. The effective number of alleles indicates that the Fulani ecotype has more effective alleles compared to the Yoruba ecotype. These results suggest that the Yoruba ecotype may be at Hardy-Weinberg equilibrium, while Fulani ecotype deviates for the ghrelin locus. In summary, our results may open opportunities for genetic improvement in Nigerian indigenous chicken due to the polymorphic nature of the ghrelin gene.